Lecturers’ perspective on project-based learning on writing skill - Maulida Maulida; Noor Aida Aflahah; Tenny Murtiningsih (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
Project-based learning (PBL) provides opportunities for students to gain knowledge, increase understanding, and acquire new skills through learning activities. By implementing it in the classroom, students can plan learning activities, determine projects to be made, solve problems, carry out tasks collaboratively, and improve their abilities. Students’ Cooperation students build attitudes and skills abilities. This study explores lecturers’ and students’ perspectives on project-based learning in writing skills classes. The type of research used in this study is case studies. The research instruments used were interviews and checklist observations. Furthermore, the research subjects were students in a writing skill class at a private university in Banjarmasin. There result shows that the lecturers consider that PBL can increase student activity in writing skill classes because by implementing PBL, students are greatly assisted in working on their writing projects. Further research is suggested to explore more students’ perspectives on PBL.